(untitled) (Revista de Crítica Literaria Latinoamericana, 2019)
This article investigates the impacts of Prudente de Moraes, neto’s conception of “sincerity” in three different occasions of Brazilian nationalist essayism: firstly on the “valorização do preto”, of Gilberto Freyre; secondly on the idealization of the “cordial man”, by Sergio Buarque de Holanda; and, finally, on the debates realized by the review Cultura Política under the years of the Estado Novo (1937- 1945). This “sincerity” does not consist in any kind of intimacy or even in some moralism promoted by the author. On the contrary, it is one of the main out- spreads of the surrealist André Breton’s poetics and of the conceps of Freud in the Brazilian context.